2011
DOI: 10.1155/2011/678101
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antifungal Activity of New α-Aminophosphonates

Abstract: α-Aminophosphonates are bioisosteres of amino acids and have several pharmacological activities. These compounds have been synthesized by various routes from reaction between amine, aldehyde, and phosphite compounds. In order to synthesize α-aminophosphonates, catalytic effect of CuCl2 was compared with FeCl3. Also all designed structures as well as griseofulvin were docked into the active site of microtubule (1JFF), using Autodock program. The results showed that the reactions were carried out in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Zahara Rezai and cowokers 24 reported one pot three component synthesis of aldehydes, amines and diethyl phosphite using FeCl 3 as catalyst (Scheme 1). Methodology was compared with the synthesis carried by using CuCl 2 , results showed that FeCl 3 is more efficient than CuCl 2 .…”
Section: Reviewmentioning
confidence: 99%
“…Zahara Rezai and cowokers 24 reported one pot three component synthesis of aldehydes, amines and diethyl phosphite using FeCl 3 as catalyst (Scheme 1). Methodology was compared with the synthesis carried by using CuCl 2 , results showed that FeCl 3 is more efficient than CuCl 2 .…”
Section: Reviewmentioning
confidence: 99%
“…[19][20][21][22][23] Therefore, considering the biological values and possibilities in the chemical modication of a-amino-phosphonates, the growing concern and the development of new organophosphorus compounds are still of great interest. [24][25][26][27][28][29][30] Plant growth testgermination, growth inhibition, dry and fresh matter…”
Section: Ecotoxicological Activitymentioning
confidence: 99%
“…Following these observations several compounds containing C–P bond attracted a considerable interest in medicinal chemistry . Among them substituted alkylphosphonates as well as derivatives with various heterocyclic systems should be mentioned …”
Section: Introductionmentioning
confidence: 99%
“…[16] Following these observations several compounds containing C-P bond attracted a considerable interest in medicinal chemistry. [17][18][19] Among them substituted alkylphosphonates [20][21][22] as well as derivatives with various heterocyclic systems should be mentioned. [23][24][25][26][27][28][29][30] In continuation of our search for biologically active 1,2,3triazoles, [31][32][33][34][35][36] a new class of (1,2,3-triazol-1-yl)quinazolin-4-ones 9 was proposed.…”
mentioning
confidence: 99%